Title Intertextuality in the Novels of Hani Ar Raheb (Green as swamps, green as fields, green as seas, as an example) - عبد القادر ناصر, سهام; كمال علوش, أماني (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The intended research is concerned with tracing out the textual relationship net of intertexualized title, in three of the writer's fictional texts , unified by the utterance " green" as well as by the theme of the freedom of the woman and its intellectual and behavioral requirement, and the imposed ideological illusion tackling the exemplary educational propensity and matrimonial institution, which is green as swamps, green as fields and green as seas. The research purposes to explore the nature of external and internal textual correlations of the intertexualized text, with the absent poetic text on the one hand, and the fictional textual body on the other, with the consequent unraveled semantic shifts and ideologic dimensions on the light of the intertextuality theory and starting from the intertextual function of the title. The survey concluded absence of explanatory function from the titles of Hani Ar Raheb's novels, and domination of symbolic feature of intertextual dimension on the entitling system, with all the consequent violation of the customary, connotation shifting, and surpassing the lexical context of the title, the matter which opened the reading and interpretation horizons up to the title's deep connotation and ideologic dimensions , to that is added the dominance of nominal sentence on the syntactical level of the three titles, and the genitive form's overdominance on their structural level, under the theory and mechanisms of intertextuality .